Evaluasi Pemantapan Transmigrasi Daerah Bergambut Tebal Rassau Jaya Kalimantan Barat - Bagus, Ida Mantra; Sutanto, Sutanto; Yahya, Irfan; Widiyanto, Widiyanto; Sastrosudarjo, Sumantri; Ronoprawiro, Sudharudjian; Dradjad, Dradjad; Maas, Azwar; Hartono, Slamet (Fakultas Geografi Universitas Gadjah Mada, 1979)
-